IMPLEMENTATION OF STAD-BASED LEARNING MODEL IN IMPROVING STUDENTS’ LEARNING OUTCOMES - Erlina Tamo Ina; Yohana Makaborang; Riwa Rambu Hada Enda (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2023)
This research was conducted with the aim of increasing student learning outcomes using the STAD learning model on the topic of human digestive system at Payeti Christian Middle School. This research is included in a Class Action Research designed by the Khemis Mc Tanggart model for this study which consists of cycle I and cycle II. Of the four stages, namely planning, implementation, observation, and reflection. The research subjects were 28 grade VIII students. The results showed that the application of the student teams achievement divisions model could improve student learning outcomes in science subjects at Payeti Christian Middle School. The enhancement of students’ learning achievements can be seen from the pre-cycle, cycle I, and cycle II through the learning carried out. This enhancement of student learning outcomes in the cognitive domain at the pre-cycle stage average value of 47.8 cycle I average value of 72.2, experienced an increase in cycle II average value of 80%. In the psychomotor aspects of the first cycle, the average value is 75, with a percentage of 80%. Meanwhile, the psychomotor aspects of cycle II averaged 89.75 with a percentage of 94%. Thus, it can be concluded that the implementation of the student teams achievement divisions model can improve student learning outcomes in biology subjects on the topic of the human digestive system at Payeti Christian Middle School.